PENGARUH EDUKASI PAJAK, LITERASI DIGITAL, SISTEM E-FILING, DAN TINGKAT PENDIDIKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (STUDI KASUS KANTOR PAJAK PRATAMA KUDUS) - Nabila Rahmawati Alamri; Zaenal Afifi; Retno Tri Handayani (Accounting Journal of Ibrahimy (AJI), 2025)
This research aimed to analyze the influence of tax education, digital literacy, e filing system, and level of education on individual taxpayer compliance. This research was conducted at the Kudus Pratama Tax Service Office using quantitative methods. Data was collected through a purposive sampling questionnaire distributed to 400 taxpayers, then analyzed using multiple linear regression and obtained using the SPSS 25 tool. The research results showed that tax education and the e-filing system and level of education had a significant positive effect on taxpayer compliance. However, digital literacy did not have a significant effect on fulfilling individual tax obligations. These findings indicated that increasing tax education and optimizing the e-filing system as well as improving one's education can increase individual taxpayer compliance.